Visual perceptual skills (non-motor) among adults in Selangor of Malaysia - Mohd Harimi Abd Rahman,; Sumithira Narayanasamy,; Ashwini S,; Mohd Fitri H,; Qiu, Ting K (Pusat Perubatan Universiti Kebangsaan Malaysia, 2020)
Visual perceptual skills are important skills for an adult to carry out their daily activities such as reading, writing and driving, successfully. This study was conducted to determine the visual perceptual skills (non-motor) of a group of adults in Selangor, Malaysia. A total of 120 subjects from Selangor with the age ranging from 20 to 59 years were randomly recruited in this cross-sectional study. This study involved distance and near visual acuity measurements using Snellen chart and Universiti Kebangsaan Malaysia (UKM) near vision chart, cognitive screening tests using the Mini Mental State Examination questionnaire (MMSE) as well as visual perceptual skills assessment (non-motor) using the Test of Visual Perceptual Skills (Non-Motor)- Revised (TVPS-R). The mean age of the subjects was 39.41+11.81 years old. Results showed that the mean standard scored obtained for Visual Discrimination (VD), Visual Memory (VM), Visual-Spatial Relationships (VSR), Visual Form Constancy (VFC), Visual Sequential Memory (VSM), Visual Figure-Ground (VFG) and Visual Closure (VC) subtests were 14.12+1.10, 13.42+1.58, 14.53+1.26, 12.47+1.03, 12.35+2.26, 13.67+1.64 and 13.73+2.23, respectively. Analysis of ANOVA shows that the VD, VM, and VSM scores are influenced by educational level (p<0.05). Pearson correlation showed a significant negative correlation between all the sub-tests of TVPS-R scores with age variation (p<0.05) except the VFC. Linear regression showed significant negative relationship between VD, VM, VSR and VSM with age. This research provided normative data of TVPS-R test on Malaysian adults for future reference and study.